Research on the integration model of quantum information technology and blockchain - Wu Jiajie; Yu Chunlin; Li Qin; Zhou Peng; Chen Yue; Cao Xi; Lv Qiwen; Zhao Tongge; Zhang Lufeng; Li Xuan (Dianzi Jishu Yingyong)
Blockchain and quantum information technology are the most cutting-edge science and technology emerging in recent years, which have received extensive attention and research in the industry. Among them, blockchain has decentralized characteristics, and applications with blockchain as the core technology have emerged in many fields such as fintech, Internet of Things, livelihood, and politics. Quantum information technology is divided into quantum computing, quantum communication, and quantum measurement. Quantum computing is mainly studied for its computational superiority compared with classical computing, and the operation speed of quantum computing has been proved to be far superior to classical computing in solving certain complex problems. While both are growing rapidly, there are issues that need to be addressed urgently. The security of blockchains is threatened because some of the classical cryptographic techniques used in blockchains have been shown to be broken by quantum computing, such as digital signatures based on asymmetric cryptographic mechanisms. To solve this problem, it has been shown that applying quantum information technology to blockchain can protect it from quantum attacks.